The relationship of masculinity and attitudes towards counseling helps among police officers in Kelang Valley - Che Sat, Noor Azeiah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The present study is a correlational research where the relationship of masculinity and attitudes towards seeking counseling help were investigated. The differences in terms of gender, ethnicity and rank with regards to the two variables mentioned earlier were also examined. Four police districts were selected randomly by using cluster sampling. Then, random sampling method was used to choose a sample of 148 police officers from these four police district offices. They comprised of 117 Malays, 16 Chinese and 15 Indians. A self-administered questionnaire was used as tool for data collection. It consisted of two scales. The Gender Role Conflict Scale (GRCS) (O’Neil, 1986) was use to measure masculinity. The Attitude Toward Seeking Professional Psychological Help Scale (ATSPPHS) (Fisher and Turner 1970; Chai, 2000) was administered to measure the attitudes towards counseling help. Correlational analyses revealed that masculinity and attitudes towards counselling help were positively correlated but it is not significant enough. The findings also show that there is no significant difference of ethnicity, gender and rank as according to masculinity and attitude towards counseling help. However, results indicate that police officers are significantly more masculine in terms of success, power, and competition compare to a person in lower rank. Other than that, finding also s shows that police officers are significantly more positive in term of their attitude towards counseling comparing to those in lower rank. As to increase the utilisation and effectiveness of Guidance and Counseling Services offers by Royal Malaysia Police in each police contingents and districts, counselors need to focus more on the issues faced by police. At the same times various steps may have to be taken as to foster more positive attitudes towards counseling services in police.